Biofeedback stimulation in the visually impaired: a systematic review of literature. (17th March 2021) - Silvestri, Valeria; Turco, Simona; Piscopo, Paola; Guidobaldi, Margherita; Perna, Fabiana; Sulfaro, Marco; Amore, Filippo
Abstract: Background: It is estimated that approximately 1.3 billion people live with some form of distance or near visual impairment. Numerous studies have been carried out to evaluate the effects of biofeedback (BF) and establish if it could be a useful tool in vision rehabilitation for various eye diseases. Objective: This systematic review aimed: 1) to examine the current evidence of BF efficacy for the rehabilitation of the visually impaired and 2) to describe methodological variations used in previous BF studies to provide recommendations for vision rehabilitation interventions. Methods: A systematic review was conducted in the Medline, PubMed, Cochrane Library and Web of Science databases to collect documents published between January 2000 and May 2020. Of the 1, 960 studies identified, 43 met the criteria for inclusion. The following information was collected from each study: sample size, control group, any eye disease, apparatus used, frequency and number of sessions of BF, main outcomes of training and whether a follow‐up was conducted. The first group included studies published as scientific articles in peer‐reviewed journals. The second group included abstracts of studies presented at peer‐reviewed conferences. Publications were also grouped according to the eye disease treated. Results: 25 articles and 18 peer‐reviewed conference abstracts (PRCAs) were included in this review. BF stimulation is a commonly used technique for the treatment of visual impairment caused by macular disease. Most BF studies evaluate the effect of training on the preferred retinal locus (PRL), particularly with regard to fixation location and stability. Across these studies, participants who received BF intervention improved fixation stability and reading speed. High variability in the number of sessions and the duration of BF training was found. Most studies did not use a control group. Conclusions: The findings of this review present evidence for biofeedback treatment in vision rehabilitation, with improved oculomotor abilities. Currently, it is not possible to formulate evidence‐based recommendations for a standard training procedure due to the poor quality of existing randomised controlled trials. High‐quality studies are needed to develop standard protocols for a range of eye diseases.